2009
DOI: 10.1210/jc.2008-1008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pituitary-Dependent Cushing’s Disease with the Multireceptor Ligand Somatostatin Analog Pasireotide (SOM230): A Multicenter, Phase II Trial

Abstract: Pasireotide produced a decrease in UFC levels in 76% of patients with Cushing's disease during the treatment period of 15 d, with direct effects on ACTH release. These results suggest that pasireotide holds promise as an effective medical treatment for this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(182 citation statements)
references
References 25 publications
7
170
0
5
Order By: Relevance
“…For some tumours (although not microadenomas), pre-TBA urinary cortisol serves as a useful marker of corticotrophinoma tumour size and functionality, and may be a useful predictor of the subsequent Nelson's syndrome development (3,33,40). However, the evidence is not conclusive, and a correlation between urinary cortisol levels and the risk of subsequent development of Nelson's syndrome has not been demonstrated in some studies (13,30,32).…”
Section: High Urinary Cortisolmentioning
confidence: 99%
“…For some tumours (although not microadenomas), pre-TBA urinary cortisol serves as a useful marker of corticotrophinoma tumour size and functionality, and may be a useful predictor of the subsequent Nelson's syndrome development (3,33,40). However, the evidence is not conclusive, and a correlation between urinary cortisol levels and the risk of subsequent development of Nelson's syndrome has not been demonstrated in some studies (13,30,32).…”
Section: High Urinary Cortisolmentioning
confidence: 99%
“…Three clinical studies have shown that pasireotide in dosages between 750 and 2400 mg/day can reduce UFC levels in patients with CD (see the 'Medical therapy for different causes of CS-Pituitary-dependent CS' section below). Induction of hyperglycemia, which may require glucose-lowering therapy, is an important side effect of pasireotide (Boscaro et al 2009, Feelders et al 2010a,b, Colao et al 2012. In healthy volunteers, pasireotide-induced hyperglycemia was shown to be due to inhibition of incretin secretion with a concomitant decreased insulin secretion (Henry et al 2011).…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%
“…Glucose levels were most effectively lowered with glucagon-like peptide 1 agonists or dipeptidyl peptidase 4 (an enzyme that inactivates the incretins) inhibitors (Henry et al 2011). Other than hyperglycemia, pasireotide might cause gastrointestinal side effects (Boscaro et al 2009, Colao et al 2012.…”
Section: Drugs With Proven Clinical Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase 2 study, pasireotide reduced mean 24-hour urinary free cortisol (UFC), serum cortisol, and plasma ACTH in patients with CD (7). Subsequently, a phase 3 study (CSOM230B2305) in CD patients demonstrated that 12 months of pasireotide not only decreased 24-hour UFC, serum and salivary cortisol, and plasma ACTH levels but also improved clinical signs and symptoms (8).…”
Section: Introductionmentioning
confidence: 99%